Using numerical modelling and experimental approaches to study the effect of dynamic valve deformations on aortic transvalvular pressure gradient - Marais, Eugéne Claude (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEng)--Stellenbosch University, 2024.